Pengaruh Model Pembelajaran Inquiry Terhadap Kecakapan Sosial dan Karakter Siswa Di MTs Negeri 1 Rantauprapat - Gultom, Maharani; Chastanti, Ika (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2020)
The purpose of this study is to find out the social skills and character of students who are taught with inquiry learning models. This type of research is a quasi-experimental design with Pretest-Posttest Group Design. The research variables include independent variables, namely the learning model and the dependent variable, namely social skills and student character. Samples were taken by purposive sampling technique. The results of the hypothesis were tested using t-tests to determine the social skills and character of the experimental class students with inquiry learning models and control classes with conventional learning. The data obtained is based on the results of the social skills questionnaire and student character questionnaire. Hypothesis test results indicate the influence of the inquiry approach to students' social skills and character.